Status sistemático y antigüedad de Megactenomys Kraglievichi Rusconi, 1930 (Rodentia, Octodontidae) - Verzi, Diego Héctor (1996)
A new cranial remain ol' a largc Ctcnomyinae from ihe Enscnadan (Earlv-Middle Plcistocene) ofthe Nccochea cliffs betwcen Costa Bonita and Puerto Quequcn (Buenos Aires Province), is describcd. The remain is assigncd to "Megactenomys'’ kraglievichi Rusconi, 1930. The revisión ofthe characters preserved in the holotype. and thc additional information given by the new material, demónstrate that this speeies is related to the extant tuco-tucos, so that it is transferred to the genus Ctenomys.